IMPLEMENTATION OF LIMITED FACE-FACE LEARNING ON STUDENT LEARNING OUTCOMES - Efendi, Yosep; Noor, Ridwan Adam M; Trismansyah, Bambang (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to see the implementation of limited face-to-face learning (PTM) during the COVID-19 pandemic on basic automotive engineering subjects at SMK NU Kaplongan. This study uses descriptive quantitative methods used to implement limited face-to-face learning, and pre-experimental (pre-experimental) to describe learning outcomes in the implementation of limited face-to-face learning. The design used in this study is a one-group pretest-posttest. The results showed that the implementation of limited face-to-face learning could significantly improve student learning outcomes. Before learning, students get a sufficient category, after strengthening the material and doing a post-test, students get a competent category. There is an increase in learning outcomes that occur in limited face-to-face learning, and there are also responses in the positive category from students regarding the implementation of limited face-to-face learning on Basic Automotive Engineering subjects (TDO Measuring Instruments)